Kajian Yuridis Urgensi Penguatan Kedudukan Masyarakat Hukum Adat dalam Mitigasi Perubahan Iklim di Indonesia - Nabilla Desyalika Putri (Journal of Law, Society, and Islamic Civilization, 2025)
Indigenous peoples possess a unique value system, local knowledge, and traditional practices that demonstrate adaptability to environmental changes, particularly in the protection of forests and natural resources. Despite their recognition in Article 18B paragraph (2) of the 1945 Constitution of the Republic of Indonesia, the protection of indigenous peoples lacks uniform standards across various environmental laws and regulations, including the forestry law, environmental law, and biological natural resource law. A notable inconsistency arises from the diverse definitions that often reflect specific sectoral or regulatory interests, resulting in a lack of a cohesive definition for indigenous peoples. Additionally, normative limitations on participation regard indigenous legal communities as either mere subjects or participants. As the impacts of climate change intensify, it is crucial for the state to engage and empower indigenous peoples as vital contributors to climate adaptation initiatives. This study employs a normative legal research that combines a statutory approach and a conceptual approach. The anticipated outcomes of this research aim to establish a foundation for more inclusive policies based on ecological justice. Ultimately, this study aims to advocate for the safeguarding of indigenous peoples' rights to land and resources, thus fostering ecological justice and enhancing environmental sustainability.